G model tested with FTSE 100 - Chiu, Yu Han (2008)
The portfolio selection is an important method of financial investment and is used to reduce the investment risks. This approach is used by investors to achieve the greater portfolio optimisation with performances of the maximum returns with the acceptable level of risks/ the minimum risks with the acceptable returns. The dissertation is concerned with the G model tested with FTSE 100 (Financial Times Stock Exchange index). Therefore, YHC Portfolio Selection Version 1.0 was designed to assist investors during the portfolio selection processes. It begins with a detailed study of the portfolio selection based on Markowitz's theory. This work has identified the FTSE 100 data from 1st January 2003 to 1st January 2006 by implementing G model. According to the characteristics of G model, the optimistic combination of securities was generated and suggested for the investors, especially those with no finance background. The objective of YHC portfolio programming is to establish and create a user friendly graphical interface that help the investors during the decision making of investment. The programming results of G model is suggested to the investors to achieve the much higher level of investment returns can be created and are contained in the portfolio selection at the lowest risk level. The YHC programming can generate the optimistic investment decisions based on the investors requirements. These include size of portfolio and various selection of industry sector.